The study of the creative potential of teenagers in the educational process - Marina I. Cheremisina; Viktoria. V Pulina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the creative development of teenagers in the educational process of the school: the relevance, regulatory framework, analyzed the methodological basis of the research problem. Psychological and pedagogic risks, insufficiency of the available pedagogical and psycho-diagnostic tools in modern science, aimed at the study of creative potential of personality of a teenager presents and analyzes the results of the ascertaining stage of the study, the ways of solution of the task.